Transcribing oral history - Bergen, Teresa (Practicing oral history, 2020)
"Transcribing Oral History offers a comprehensive guide to the transcription of qualitative interviews, an often richly debated practice within the oral history field. Based upon the author's personal experience as a freelance transcriptionist and interviews with more than 30 professionals working around the world in the oral history and qualitative research fields, it is an indispensable guide for those involved in interviews and transcription at any level of an oral history project, including historians, transcriptionists, interviewers, project administrators, archivists, researchers and students"--